EXPLORING THE THERAPEUTIC POTENTIAL OF VISUAL ARTS: A NON-VERBAL LANGUAGE FOR EXPRESSING EMOTIONS IN ART THERAPY - Rathaur, Anuj Kumar Singh (International Journal of Research -GRANTHAALAYAH, 2025)
This research study explores the therapeutic function of visual arts as a non-verbal form of emotional expression within art therapy. As a form of psychotherapy utilizing the creative possibilities of visual art, art therapy aims to facilitate emotional exploration and promote healing. This study examines the efficacy of visual arts as a means of non-verbal emotional communication in therapeutic contexts by analyzing case studies, experimental data, and theoretical frameworks. It investigates how cultural and individual differences influence creative expression and its impact on emotional transmission. Additionally, the study explores the outcomes of employing art therapy methods across diverse demographics, including children, adolescents, adults, and elderly individuals, within both clinical and non-clinical settings. Ultimately, this research study seeks to deepen our understanding of the therapeutic potential of visual arts, particularly regarding their capacity for emotional expression and healing in mental health contexts.